KEMAMPUAN BERPIKIR KRITIS MATERI PANJANG DAN BERAT DENGAN PERMAINAN SNAKES LADDER PADA SISWA SDN TELUK TIRAM 2 - Mentari Giri Saputri; Darmiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study identified that some third-grade students at SDN Teluk Tiram 2 had difficulty grasping math concepts and that the instructional methods were not sufficiently diverse. To address these issues, a Problem Based Learning (PBL) model was integrated with Realistic Mathematics Education (RME) and Team Games Tournament (TGT). The study aimed to describe both teacher and student activities and evaluate critical thinking skills and learning outcomes related to units of length and weight. Conducted as a Classroom Action Research (PTK) over three sessions with 25 students, the results revealed that by the final session, teacher activity was rated as “Very Good,” student activity was “Very Active,” students' critical thinking skills were categorized as “Skilled” and “Very Skilled,” and student learning outcomes met the criteria for classical completeness. The researcher recommended this combined model as an effective approach to enhance future learning processes.